PERFORMANCE DETERMINANTS OF STATE CIVIL SERVICES (ASN) IN THE COVID-19 PANDEMIC - Siti Nurhusna; Wahyudi Wahyudi (Universitas Pamulang, 2021)
Since the Covid-19 outbreak in May 2020 there has been a shift in work patterns and systems in various agencies and companies, including the government. This is done as a form of adaptation to the situation, especially in preventing the spread of the Covid-19 virus. But on the other hand the organization must continue to run, therefore there is a work from home work model. This concept exists because of circumstances, so that various shortcomings arise, one of which is work activities do not run effectively and have an impact on decreasing employee performance. In fact, this research was conducted to find out this phenomenon, and what factors have linearity on employee performance. The research method used in answering the research hypothesis is quantitative with statistical regression (forecasting). The research sample was BPPT employees totaling 80 people, with a simple random sampling technique. The results of the study recommend that the model that best improves performance during the pandemic is the simultaneous model. This means that factors directly related to employee performance have a major impact on improving performance, including high morale, proportional workload, and career openness. In other words, institutions must be sensitive to the determinants of performance, both under normal circumstances or in a pandemic.